Gut endoderm is involved in the transfer of left-right asymmetry from the node to the lateral plate mesoderm in the mouse embryo - Saund, Ranajeet S. (Company of Biologists, 2012)
In the mouse, the initial signals that establish left-right (LR) asymmetry are determined in the node by nodal flow. These signals are then transferred to the lateral plate mesoderm (LPM) through cellular and molecular mechanisms that are not well characterized. We hypothesized that endoderm might play a role in this process because it is tightly apposed to the node and covers the outer surface of the embryo, and, just after nodal flow is established, higher Ca(2+) flux has been reported on the left side near the node, most likely in the endoderm cells. Here we studied the role of endoderm cells in the transfer of the LR asymmetry signal by analyzing mouse Sox17 null mutant embryos, which possess endoderm-specific defects. Sox17(–/–) embryos showed no expression or significantly reduced expression of LR asymmetric genes in the left LPM. In Sox17 mutant endoderm, the localization of connexin proteins on the cell membrane was greatly reduced, resulting in defective gap junction formation, which appeared to be caused by incomplete development of organized epithelial structures. Our findings suggest an essential role of endoderm cells in the signal transfer step from the node to the LPM, possibly using gap junction communication to establish the LR axis of the mouse.